Relationship between Selected Personal Determinants and Examination Cheating among Kenyan Secondary School Students - Owenga, John Timon Odhiambo; Aloka, Peter J. O.; Raburu, Pamela A. (Academic Journal of Interdisciplinary Studies, 2018)
The present study investigated the relationship between selected personal determinants and examination cheating among Kenyan secondary school students. This study used a Sequential Explanatory design. The target population was 51,900 students in Kisumu County within 153 public secondary schools categorized as 2 National secondary schools, 21 extra county schools, and 130 county and sub-county schools. A simple random sampling technique was used to determine sample size which comprised of 380 respondents since the study was confined within specific ecological boundary which was public secondary schools. Data collection instruments included questionnaires, for general data collection from the respondents and in-depth interview schedules for one to one interview of respondents. The finding of the study shows that there was statistically significant positive correlation (r=.592, n=360, p<.05) between Personal determinants and overall perceived level of exams cheating. It is evident from the model that student personal characteristics accounted for 35.1%, as signified by coefficient R2 = .351, of the variation in perceived level of examinations cheating among students in secondary schools. it is evident that gender made the highest (Beta=.467) contribution as personal determinant on explaining the dependent variable, when the variance explained by all other variables in the model was controlled for. Student self-esteem had the least effect (Beta=.048) on examinations cheating. However, all the personal determinants had statistically significant influence on examinations cheating among the secondary schools students. The calculated effect size (eta squared=.3514) indicate that there was quite a substantial amount of variance in level of examinations cheating caused by variability in the personal determinants of the students. This suggests that 35.1% of the variance in the perceived exams cheating was accounted for by the personal determinants of the secondary school students, when other variables were controlled. Teacher counselors to assess and identify those students at risk and change their perception on examination cheating due to low self-efficacy.
Keywords: Personal determinants; examination cheating; Kenyan; secondary school students; self-esteem; self-efficacy; locus of control; gender